Invariants of coinvariant algebras - Smith, Larry (Forum mathematicum, 2015)
Let be a representation of a finite group over the field 𝔽 and let be a subgroup of . Form the algebra of polynomial functions on the representation space of ρ. The action of on extends to and we denote by the ; namely, the subalgebra of -invariant forms. The of ρ is the quotient algebra where the of (or better put, of ρ) is the ideal of generated by all the homogeneous -invariant forms of strictly positive degree. The group acts on and the subject of this manuscript is the algebra of -invariants of